Application of markov model to estimate individual condition parameters for transformers - Selva A.M.; Azis N.; Yahaya M.S.; Ab Kadir M.Z.A.; Jasni J.; Ghazali Y.Z.Y.; Talib M.A. (MDPI AG, 2023)
Carbon dioxide; Carbon monoxide; Electric breakdown; Ethylene; IEEE Standards; Markov processes; Nonlinear programming; Probability distributions; Statistical tests; Absolute error; Chi-square tests; Condition parameters; Condition-based monitoring; Markov model; Non-linear optimization; Parameter estimation